PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM TRANSAKSI ONLINE DI BALI - Mas Dianastiti, Made Mahayu; Markeling, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013, 2013)
Technology information that has a quick progress in Indonesia already made a change of humans behavior in their lives. Besides has a role in human civilization, technology information progress also make a set of law problems, one of them is deception that caused by the seller in online shop. This paper aim to answer the question about what kind of law protection that can be used for the consumers in online shop in Bali island. The legal research used is normative legal research. The result and conclusion that obtained by this research is Act Number 8 of 1999 about Consumer Protection as a product of law can protect the consumers be guided by Article 8 and Article 16.
Keywords: technology information progress, online transaction, deception, consumers protection